ANALISIS IMPLEMENTASI FULL DAY SCHOOL TERHADAP RESPON ORANG TUA SISWA SEKOLAH DASAR ISLAM TERPADU (SDIT) SAMAWA CENDEKIA KABUPATEN SUMBAWA - Saleh, Muhammad; Hakim, Lukamanul (Jurnal TAMBORA, 2020)
The full day school system is implemented to facilitate students with strategiesand methods that provide active and enjoyable learning. Activitiesfull day learning can build interpersonal intelligence such as sensitivitysocial, social understanding and social communiction (social communication). Researchaims to analyze the implementation of a full day school system for buildinginterpersonal intelligence of students, the role of teachers and school members in buildingstudents' interpersonal intelligence, and the barriers faced by teachers and schools dalancarry out a full day school system. The research method used is a methodqualitative. The population of this study were all students and parents of SDIT studentsSamawa scholars, amounting to 1244 people. The number of samples of this study was 33people from the total population. Data collection techniques, namely documentation, questionnaires, anddocuments from school principals, and teachers. This research data analysis technique appliespercentage descriptive analysis. Based on the results of data analysis that implementationthe full day shool system to the response of parents of students at the Integrated Islamic Primary SchoolSumbawa Scholar is very significant. The reason is the implementation of the full day school systembuild intelligence both planting social attitudes and social communication as wellexemplary.